Evaluation of plasma reactive oxygen metabolites levels in obese subjects with periodontal disease - Suresh, Snophia; Mahendra, Jaideep; Sudhakar, Uma; Pradeep, A; Singh, Gurdeep (Indian journal of dental research, 2016)
Background: Obesity represents the systemic condition capable of influencing the onset and progression of periodontal disease. Obesity is associated with oxidative stress. Plasma level of reactive oxidative metabolites (ROMs) is measured as an indicator of oxidative stress in the body. The aim of this study is to assess and compare the plasma ROM levels in obese subjects with healthy and inflammatory periodontal status. Materials and Methods: Sixty subjects selected were grouped as 15 obese or overweight subjects with generalized chronic periodontitis, 15 obese or overweight subjects with generalized chronic gingivitis, 15 obese or overweight subjects with healthy periodontium, and 15 nonobese and healthy periodontium. The clinical periodontal parameters such as plaque index, gingival index, probing pocket depth, and clinical attachment level were measured. Blood samples were obtained to measure the plasma levels of ROM. Result and Conclusion: In this study, obese subjects with chronic periodontitis (Group I) had mean plasma ROM levels (442.3 ± 15.65 Carratelli unit [CARR U]) showing 100% subjects with high oxidative stress. Obese subjects with chronic gingivitis (Group II) had mean plasma ROM levels (358.7 ± 20.61 CARR U) indicating 86.7% subjects with oxidative stress. Obese subjects with healthy periodontium (Group III) had 46.7% subjects with slight oxidative stress, and the mean ROM level was 320.2 ± 17.57. Nonobese subjects with healthy periodontium (Group IV) had 80% of subjects with normal oxidative stress and the mean plasma ROM level was 296.9 ± 20.35 CARR U. The intra- and inter-group comparison showed significant difference (P < 0.001). From our study, we report that obese subjects with periodontitis have more oxidative stress compared to obese subjects with healthy periodontium.